Sol-gel preparation method of NiFeMn-based layered metal oxide sodium ion battery positive electrode material
By controlling the pH value of citric acid in the sol-gel method of the positive electrode material of sodium ion battery, the complexation of metal ions is solved, the problem of uneven element dispersion is improved, the grain uniformity and electrochemical performance are improved, and the material is improved cyclic stability and rate performance, and reduce production energy consumption.
Patent Information
- Application Number
- CN202411423815.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the synthesis of the existing transition metal layered sodium oxide battery positive electrode material sol-gel method, the complexing agent has different complexing abilities from different metal elements, resulting in uneven dispersion of elements, affecting grain size and uniformity, thus limiting the Electrochemical properties and cyclic stability of electrode materials.
By controlling the pH value of citric acid, in the process of synthesising NaNi1/3Fe1/3Mn1/3O2 in the sol-gel method, the complexation constant of each metal ions is balanced to make them uniformly coupled, shorten the solid phase reaction rate and reduce the grain size. Increase the specific surface area and improve the electrochemical performance and cyclic stability of the electrode material.
The uniformity of element distribution is achieved, the solid phase reaction time is shortened, the grain size is reduced, the rate performance and cycle stability of the positive electrode material of sodium ion battery are improved, and the production energy consumption is reduced.
Smart Images

Figure CN119306263A_ABST
Abstract
Description
Technical Field
[0001] The sol-gel method of sodium nickel iron manganese oxide for sodium ion batteries of the present invention belongs to the preparation method of secondary battery positive electrode materials in energy materials. Background Art
[0002] Lithium-ion batteries have the characteristics of high energy density, long life, and high energy transfer efficiency. They dominate the portable electronic product market and have broad application prospects in the field of electric vehicles. However, due to the limitation of lithium resources, the price of lithium has risen sharply in recent years, which has limited its application in energy storage devices. Sodium is abundant and has similar physical and chemical properties to Li. At the same time, the working principle and production process of sodium-ion batteries are also similar to those of lithium-ion batteries, so sodium-ion batteries are expected to become an effective substitute for lithium-ion batteries.
[0003] At present, the cathode material is the key component that provides sodium ions in the whole battery and determines the battery potential difference. The performance of the cathode material significantly affects the overall performance of the sodium-ion battery. The cathode materials of sodium-ion batteries with high specific capacity and stable cycle have become the bottleneck of the development of sodium-ion batteries. Over the years, different material systems have been born for the cathode materials of sodium-ion batteries, including transition metal layered oxide materials (Na x TMO2), polyanionic materials (Na x M y (XO4) n ) and Prussian blue (A x M[Fe(CN)6] (1-y) ·y·nH2O) and their analogs (such as Prussian white), these three types of materials each have their own advantages and disadvantages in electrochemical applications. Prussian blue / white analog positive electrodes have excellent long cycle life, but they are difficult to synthesize and difficult to produce on a large scale commercially. The large relative molecular weight of polyanion materials limits their commercial application scenarios. Layered transition metal oxide positive electrodes can provide a theoretical sodium ion storage capacity of more than 200mAh / g at a relatively high (>3.0V) average potential, and the preparation process is compatible with lithium ternary batteries, making them the first choice for commercial sodium ion batteries.
[0004] The sol-gel method has unique advantages in synthesizing positive electrode materials for sodium ion batteries. First, it has high chemical uniformity, which can achieve uniform dispersion of metal ions at the molecular level, and contribute to the homogenization of the components in the final product; secondly, the sol-gel method allows fine control of reaction conditions (such as pH value, temperature, salt concentration, etc.) to form a specific microstructure and morphology and control porosity and specific surface area; finally, the sol-gel method is suitable for the synthesis of various types of transition metal layered oxide precursors, and the synthesis is simple and does not require complex equipment. For example, the invention application with application number CN 114873575 A discloses a precursor that uses citric acid as a complexing agent and a gelling agent to generate a homogeneous precursor. After heat treatment, the specific capacity of the material can reach more than 100mAh / g. There is also an invention application with application number CN 200610096873.2 that discloses a patent for synthesizing sodium ferrous phosphate by a sol-gel method, which uses citric acid as a complexing agent and uses ammonia water to adjust the pH value to 7-8. The first discharge capacity of the electrode material after heat treatment reaches 91 mAh / g, and the discharge capacity after 20 cycles is 81.7 mAh / g.
[0005] However, the above technology has the problem that the different complexing abilities of the complexing agent with different metal elements lead to uneven element dispersion, hindering the solid phase reaction kinetics process and affecting the grain size and uniformity. Summary of the invention
[0006] The purpose of the present invention is to solve the problem of uneven element dispersion caused by different complexing abilities of complexing agents with different metal elements in the existing transition metal layered oxide sodium ion battery positive electrode material sol-gel synthesis process, which hinders the solid phase reaction kinetic process and affects the grain size and uniformity, and provide a sol-gel preparation method for NiFeMn layered metal oxide sodium ion battery positive electrode material. On the basis of existing research, the present invention further optimizes the technical details, balances the complexing constants of each metal ion, enables it to be evenly coupled with the complexing agent, achieves the purpose of uniform dispersion, and then accelerates the solid phase reaction rate, reduces the grain size, and increases the specific surface area. Further improve the electrochemical performance of the electrode material, enhance the rate performance and cycle stability.
[0007] The present invention proposes a more effective method, using NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3O2 as an example, the synthesis of NaNi by sol-gel method 1 / 3 Fe 1 / 3 Mn 1 / By controlling the pH value of the complexing agent (citric acid) during the preparation of 3O2, a transition metal layered oxide sodium ion battery positive electrode material with uniformly dispersed elements, uniform and controllable grain size, and stable electrochemical properties can be obtained.
[0008] The sol-gel preparation method of the NiFeMn-based metal oxide sodium ion battery positive electrode material of the present invention is as follows:
[0009] 1) Weigh CH3COONa·3H2O, Ni(CH3COO)2·4H2O, FeN3O9·9H2O, (CH3CO2)2Mn·4H2O;
[0010] 2) According to m (H2O) =(n (CH3COONa·3H2O) +n (Ni(CH3COO)2·4H2O) +n (FeN3O9·9H2O) +n ((CH3CO2)2Mn·4H2O) )*M (H2O) * Weigh 50% deionized water, add the salt weighed in step 1) into the deionized water, mix well, and obtain solution A;
[0011] 3) According to m (C6H8O7) =(n (CH3COONa·3H2O) +n (Ni(CH3COO)2·4H2O) +n (FeN3O9·9H2O) +n ((CH3CO2)2Mn·4H2O) )*M (C6H8O7) *(1.5~2.0) weigh anhydrous citric acid and add it to deionized water to prepare solution B;
[0012] 4) preparing an aqueous ammonia solution as solution C;
[0013] 5) adding solution C to solution B, mixing well, and then adding to solution A, heating and stirring to obtain a dry gel, and drying to obtain a precursor;
[0014] 6) After calcining the precursor, grinding it, and then calcining it, a NiFeMn-based transition metal layered oxide Na x Ni y Fe z Mn (4-x-2y-2z) O2;
[0015] Where m is NiFeMn-based transition metal layered oxide Na x Ni y Fe z Mn (4-x-2y-2z) O2 mass, n is NiFeMn-based transition metal layered oxide Na x Ni y Fe z Mn (4-x-2y-2z) The amount of O2 substance, M is NiFeMn-based transition metal layered oxide Na x Ni y Fe z Mn (4-x-2y-2z) O2 molar mass.
[0016] Furthermore, in step 4), the ammonia solution is prepared by weighing NH3·H2O and H2O in a volume ratio of not less than 2:1.
[0017] Furthermore, in step 5), the conditions for obtaining the dry gel by heating and stirring are that the rotation speed is not less than 500 rpm and the temperature is not higher than 90°C.
[0018] Furthermore, in step 5), the drying conditions are a temperature of 120° C. to 200° C. and a heat preservation time of not less than 10 hours.
[0019] Furthermore, in step 6), the precursor is calcined and then ground, and the calcination conditions are a temperature of 400° C. to 550° C. and a holding time of not less than 6 hours.
[0020] Furthermore, in step 6), the re-calcination conditions are 840-860° C. and the insulation time is greater than 12 h to 15 h.
[0021] Furthermore, in step 4), solution C is added to solution B, the pH value is adjusted to 2.5-3.5, and the mixture is mixed.
[0022] The present invention has the following beneficial effects:
[0023] The present invention effectively balances the metal ion Na by controlling the pH value of the complexing agent. + 、Ni 2+ , Fe 3+ , Mn 2+ The complexation rate and order of the same complexing agent make the element distribution more uniform, shorten the distance and time of the solid phase reaction, thereby reducing the grain size and increasing the rate performance and cycle stability of the positive electrode material of the sodium ion battery. At the same time, because the solid phase reaction is accelerated, the calcination temperature is effectively reduced from 900°C to 850°C, effectively reducing production energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The XRD patterns of Example, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4 and Comparative Example 5 are shown;
[0025] Figure 2 The SEM scanning electron microscope images (40000 times) of Example, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4 and Comparative Example 5 are shown in FIG.
[0026] Figure 3 The SEM images of Example and Comparative Example 5 (40000 times and 20000 times);
[0027] Figure 4 The eds spectrum diagram of the embodiment;
[0028] Figure 5is the eds spectrum of comparative example 1;
[0029] Figure 6 is the eds spectrum of comparative example 2;
[0030] Figure 7 is the eds spectrum of comparative example 3;
[0031] Figure 8 It is the eds spectrum of comparative example 4;
[0032] Fig. 9 The cycle performance diagrams of Example, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 are shown;
[0033] Fig.10 It is the rate performance diagram of Example, Comparative Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4. DETAILED DESCRIPTION
[0034] In order to make the objectives, technical solutions and advantages of the embodiments of the present invention more clearly understood, the spirit of the contents disclosed by the present invention will be described in detail below. After understanding the embodiments of the contents of the present invention, any technician in the relevant technical field can change and modify them according to the techniques taught by the contents of the present invention without departing from the spirit and scope of the contents of the present invention.
[0035] The exemplary embodiments of the present invention and the description thereof are used to explain the present invention, but are not intended to limit the present invention.
[0036] Example
[0037] (1) Prepare solution A, solution B, and solution C.
[0038] (2) Solution C was added to solution B, and its pH value was adjusted to 3. Then, solution C was added to solution A, and heated and stirred at 80°C at 500 rpm until a dry gel was obtained. The dry gel was dried at 120°C for 10 h to obtain a precursor with uniform element distribution.
[0039] (3) The precursor was calcined at 500 °C for 6 h, taken out, ground for 30 min, and then calcined at 850 °C for 12 h to obtain the target product NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3O2 transition metal layered oxide.
[0040] Comparative Example 1
[0041] (1) Prepare solution A.
[0042] (2) Solution A was heated at 80° C. at 500 rpm and stirred until a dry gel was obtained, and the dry gel was dried at 120° C. for 10 h to obtain a precursor.
[0043] (3) The precursor was calcined at 500 °C for 6 h, taken out, ground for 30 min, and then calcined at 850 °C for 12 h to obtain the target product NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3O2 transition metal layered oxide.
[0044] Comparative Example 2
[0045] (1) Prepare solution A and solution B.
[0046] (2) Add solution B to solution A, heat and stir at 80°C at 500 rpm until a dry gel is obtained, and dry the dry gel at 120°C for 10 h to obtain a precursor.
[0047] (3) The precursor was calcined at 500 °C for 6 h, taken out, ground for 30 min, and then calcined at 850 °C for 12 h to obtain the target product NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3O2 transition metal layered oxide.
[0048] Comparative Example 3
[0049] (1) Prepare solution A, solution B, and solution C.
[0050] (2) Solution C was added to solution B and its pH value was adjusted to 6. Then, solution C was added to solution A and heated at 80°C with stirring at 500 rpm until a dry gel was obtained. The dry gel was dried at 120°C for 10 h to obtain a precursor with uniform element distribution.
[0051] (3) The precursor was calcined at 500 °C for 6 h, taken out, ground for 30 min, and then calcined at 850 °C for 12 h to obtain the target product NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3O2 transition metal layered oxide.
[0052] Comparative Example 4
[0053] (1) Prepare solution A, solution B, and solution C.
[0054] (2) Solution C was added to solution B, and its pH value was adjusted to 9. Then, solution C was added to solution A, and heated and stirred at 80°C at 500 rpm until a dry gel was obtained. The dry gel was dried at 120°C for 10 h to obtain a precursor.
[0055] (3) The precursor was calcined at 500 °C for 6 h, taken out, ground for 30 min, and then calcined at 850 °C for 12 h to obtain the target product NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3O2 transition metal layered oxide.
[0056] Comparative Example 5
[0057] (1) Prepare solution A, solution B, and solution C.
[0058] (2) Solution C was added to solution B, and its pH value was adjusted to 9. Then, solution C was added to solution A, and heated and stirred at 80°C at 500 rpm until a dry gel was obtained. The dry gel was dried at 120°C for 10 h to obtain a precursor.
[0059] (3) The above precursor was calcined at 500°C for 6 hours, taken out, ground for 30 minutes, and then calcined at 900°C for 12 hours to obtain the target product NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3O2 transition metal layered oxide.
[0060] Button cell assembly and electrochemical performance testing:
[0061] The specific technical solution is:
[0062] The positive electrode material, conductive agent (Super-P) and binder (polyvinylidene fluoride) obtained in the comparative example and comparative examples 1 to 5 were mixed and ground at a mass ratio of 8:1:1, and then added to N-methyl-2-pyrrolidone for mixing and grinding. The slurry was then evenly coated on aluminum foil and vacuum dried at 60°C for 12 hours. Finally, the electrode was pressed with a double roller. A metal sodium sheet was used as the positive electrode, the electrolyte was NaPF6, and the diaphragm was a glass fiber membrane. A CR2032 button battery was assembled in an argon-filled glove box for electrochemical testing.
[0063] Figure 1 . are the XRD patterns of Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4 and Comparative Example 5. The X-ray diffraction results clearly show that the materials obtained using different synthesis conditions are all O3 phase transition metal layered oxides, belonging to the R3m space group, indicating that whether a complexing agent (citric acid) is added or not, and whether the pH value is changed will not have a significant effect on the final material phase, which is in line with expectations.
[0064] Figure 2 The scanning electron microscope (SEM) images of the embodiment and four control groups (Comparative Example 1 to Comparative Example 4) in this study are shown, and all images show a regular polygonal lamellar structure. Specifically, Figure 2 (a) is a SEM image of the embodiment, showing that the polygonal flakes of the material are of uniform size, with clear boundaries, no significant agglomeration, and a grain size of about 1 micron, which meets the characteristics of an ideal O3-type transition metal layered oxide. In contrast, Figure 2The SEM image of Comparative Example 1 shown in (b) shows blurred flake edges, uneven size distribution and severe agglomeration, indicating a low degree of crystallinity. Figure 2 (c) shows the SEM image of comparative example 2. Although the hexagonal lamellar boundaries are clearly visible, the grain sizes are uneven. In some areas, smaller grains are attached to large grains larger than 2 μm, which suggests the uneven distribution of elements in the sol-gel process. Figure 2 (d) The corresponding SEM image of Comparative Example 3 reveals a trend of further reduction in grain size, accompanied by uneven grain size and insufficient crystallinity. This finding is consistent with Figure 4 The results are consistent with those observed in , indicating a significant deviation in the element distribution in the sol-gel phase. Figure 2 Although the sample of comparative example 4 represented by (e) exhibits clear hexagonal lamellar boundaries, it still has problems of inconsistent grain size and agglomeration. In general, the embodiment performs best in terms of consistency of grain size and clarity of grain boundaries, and has excellent crystallinity. This is due to the fact that the uniformity of element distribution in the sol-gel process is close to the expected design ratio, thereby promoting the kinetic process of the solid phase reaction, reducing the grain size, increasing the number of active sites for electrochemical reactions, and significantly improving the electrochemical performance of the material.
[0065] Figure 3 Scanning electron microscope (SEM) images of the embodiment and comparative example 5 are provided. It is worth noting that both comparative example 5 and the embodiment adopt the reaction condition of pH value 3, but when the calcination temperature is set to 900°C, there is a significant difference between the two. Figure 3 (c) and (d) show that compared with the example, the grain size in comparative example 5 shows great inconsistency, ranging from more than 2 microns to less than 200 nanometers. This phenomenon may be attributed to the secondary crystallization effect at high temperature. An important innovation of this study is that for Na 1 / 3 Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 For transition metal layered oxide materials such as O2, the traditional process usually uses 900℃ as the calcination temperature. However, by finely controlling the reaction conditions, we have achieved further uniformity of element distribution, promoted the solid-phase reaction process, and successfully lowered the required calcination temperature. This achievement not only demonstrates the potential for process improvement, but also provides a new perspective for subsequent research.
[0066] Figures 4 to 8Energy dispersive X-ray spectroscopy (EDS) images of the embodiment and comparative examples 1 to 4 in this study are shown. The observation area is more than 100 microns, which effectively eliminates the influence of instrument errors. These spectra describe the distribution of individual elements in the sample in detail. Through statistical analysis of signal intensity, this embodiment summarizes Table 1, which lists Figures 4 to 8 The results show that only the atomic ratio of the elements in the embodiment is closest to the designed ratio (Ni:Fe:Mn:Na=1:1:1:3). For Comparative Example 1, the Na content is significantly lower than the expected ratio, which is not conducive to the crystallization process during the solid phase reaction. Figure 2 (b) shows that the absence of a complexing agent would hinder the Na + In Comparative Example 2, the proportion of Mn element is low. 2+ The importance of forming a layered structure is that its uneven distribution will lead to differences in grain growth rates during crystallization, resulting in significant differences in grain size. It also suggests that it is not conducive to the uniform dispersion of Mn elements without adjusting the pH value. The reaction pH value of Comparative Example 3 is 6. Under this condition, the content of Na element far exceeds the designed ratio, indicating that at this pH value, Na + The preferred complex formation with citrate ions leads to uneven element distribution. The pH value of the reaction environment of Comparative Example 4 is 9, that is, the solution is in a weakly alkaline state. At this time, the Fe content is twice the design value, which indicates that the uniform complexation between elements such as Ni, Fe, Mn, and Na is not conducive to under alkaline conditions. In summary, the embodiment with a pH value of 3 shows a high uniformity of element distribution, which basically meets the predetermined design ratio and is conducive to crystal formation during the solid phase reaction process. Figure 2 As shown in (a), the embodiment shows good characteristics of uniformity of grain size and no agglomeration.
[0067] Fig. 9 The specific capacity curves obtained from the charge-discharge cycle tests of the embodiments and control groups 1 to 4 at a constant current density of 150 mA / g are shown. As shown in the figure, the embodiments exhibit significant initial capacity and excellent cycle stability. In contrast, due to the low crystallinity and obvious agglomeration of the material in control group 1, its initial capacity is low. Control groups 2 and 3 performed similarly in terms of initial capacity and cycle stability. It is worth noting that although control group 4 exhibited the highest initial capacity, due to the formation of secondary grains, its capacity decay rate was faster, showing poor cycle stability. These findings further confirm the importance of optimizing the synthesis reaction conditions for improving the electrochemical properties of materials. Fig.10The charge and discharge capacities of the embodiment and control groups 1 to 4 at different current densities were compared. The results showed that the embodiment could still maintain a relatively high capacity (more than 65% of the capacity at 0.1C) at a high current density (e.g., 5C), demonstrating excellent rate performance; while control groups 1 to 4 all showed weak rate performance under this condition.
[0068] As described above, in the process of preparing NiFeMn layered oxide sodium ion battery positive electrode materials by sol-gel method, by controlling the pH value of the complexing agent to the range of 3 to 5, the crystallinity of the material can be significantly improved, forming a smaller grain size and a larger specific surface area. These factors together promote the material to exhibit excellent electrochemical properties, including high initial specific capacity and good cycle stability. Therefore, the synthesis conditions proposed in this study are of great significance for the development of high-performance layered oxide sodium ion battery materials.
Claims
1. A sol-gel preparation method for a NiFeMn-based metal oxide sodium ion battery positive electrode material, characterized in that The preparation method is as follows: 1) Weigh CH3COONa·3H2O, Ni(CH3COO)2·4H2O, FeN3O9·9H2O, (CH3CO2)2Mn·4H2O; 2) According to m (H2O) =(n (CH3COONa·3H2O) +n (Ni(CH3COO)2·4H2O) +n (FeN3O9·9H2O) +n ((CH3CO2)2Mn·4H2O) )*M (H2O) * Weigh 50% deionized water, add the salt weighed in step 1) into the deionized water, mix well, and obtain solution A; 3) According to m (C6H8O7) =(n (CH3COONa·3H2O) +n (Ni(CH3COO)2·4H2O) +n (FeN3O9·9H2O) +n ((CH3CO2)2Mn·4H2O) )*M (C6H8O7) *(1.5~2.0) weigh anhydrous citric acid and add it to deionized water to prepare solution B; 4) preparing an aqueous ammonia solution as solution C; 5) adding solution C to solution B, mixing well, and then adding to solution A, heating and stirring to obtain a dry gel, and drying to obtain a precursor; 6) After calcining the precursor, grinding it, and then calcining it, a NiFeMn-based transition metal layered oxide Na x Ni y Fe z Mn (4-x-2y-2z) O2; Where m is NiFeMn-based transition metal layered oxide Na x Ni y Fe z Mn (4-x-2y-2z) O2 mass, n is NiFeMn-based transition metal layered oxide Na x Ni y Fe z Mn (4-x-2y-2z) The amount of O2 substance, M is NiFeMn-based transition metal layered oxide Na x Ni y Fe z Mn (4-x-2y-2z) O2 molar mass.
2. The sol-gel preparation method of the NiFeMn-based metal oxide sodium ion battery positive electrode material according to claim 1, characterized in that In step 4), the ammonia solution is prepared by weighing NH3·H2O and H2O in a volume ratio of not less than 2:
1.
3. The sol-gel preparation method of the NiFeMn-based metal oxide sodium ion battery positive electrode material according to claim 1, characterized in that In step 5), the conditions for obtaining the dry gel while heating and stirring are that the rotation speed is not less than 500 revolutions and the temperature is not higher than 90°C.
4. The sol-gel preparation method of the NiFeMn-based metal oxide sodium ion battery positive electrode material according to claim 1, characterized in that In step 5), the drying conditions are a temperature of 120° C. to 200° C. and a heat preservation time of not less than 10 hours.
5. The sol-gel preparation method of the NiFeMn-based metal oxide sodium ion battery positive electrode material according to claim 1, characterized in that In step 6), the precursor is calcined and then ground. The calcination conditions are a temperature of 400° C. to 550° C. and a holding time of not less than 6 hours.
6. The sol-gel preparation method of the NiFeMn-based metal oxide sodium ion battery positive electrode material according to claim 1, characterized in that In step 6), the re-calcination conditions are 840-860° C. and the insulation time is greater than 12 h to 15 h.
7. The sol-gel preparation method of the NiFeMn-based metal oxide sodium ion battery positive electrode material according to claim 1, characterized in that In step 4), solution C is added to solution B, the pH value is adjusted to 2.5-3.5, and mixed.
Citation Information
Patent Citations
O3-type sodium ion battery positive electrode material and preparation method and application thereof
CN110277555A
P2 type layered sodium ion battery positive electrode material and preparation method thereof
CN113921809A
Laminated positive electrode material of P3 type sodium ion battery as well as preparation method and application of layered positive electrode material
CN114122382A